2009
DOI: 10.1002/mar.20302
|View full text |Cite
|
Sign up to set email alerts
|

Product involvement in organic food consumption: Does ideology meet practice?

Abstract: This study assesses the level of consumers' felt involvement in four distinct product categories of organic food (coffee, bread, fruit, and flour), and examines the role of felt involvement in the broader context of organic food shopping behavior. It is shown that the reason why consumers do not buy organic food regularly despite their positive attitudes is that such ideologically formed attitudes are not present in habitual, low-involvement shopping activities with limited problem-solving needs as in food sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
113
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 55 publications
11
113
0
2
Order By: Relevance
“…Academic implications: The study validated the results of earlier researchers that have identified environmental and health concerns as key drivers of organic consumption (Tarkiainen and Sundqvist, 2009;Magistris and Gracia, 2008). However, the study also reported the existence of a socially concerned group of consumers who are driven by popular opinion.…”
Section: Discussion Of Results and Implicationssupporting
confidence: 82%
See 1 more Smart Citation
“…Academic implications: The study validated the results of earlier researchers that have identified environmental and health concerns as key drivers of organic consumption (Tarkiainen and Sundqvist, 2009;Magistris and Gracia, 2008). However, the study also reported the existence of a socially concerned group of consumers who are driven by popular opinion.…”
Section: Discussion Of Results and Implicationssupporting
confidence: 82%
“…McEachern and McClean (2002) found that organic decisions were more self-interest driven-consumers looked for taste, food safety and health benefits rather than altruistic. Others found that both environmentally and health related values are equally instrumental in formulating a positive attitude towards organic food products (Tarkiainen and Sundqvist, 2009;Magistris and Gracia, 2008). Nasir and Karakya (2014) found that socially responsible consumption, health orientation, hedonic and utilitarian consumption were important predictors of organic buying decisions.…”
Section: Predicting Organic Purchase: Role Of Consumer-related Factorsmentioning
confidence: 99%
“…It supports investigations of choice processes prior to awareness, even by the person making the choice. Food choice and eating are often considered "mindless," as they are low involvement activities (Tarkiainen & Sundqvist, 2009;Wansink, Just, & Payne, 2009). Employing eye-tracking technique to understand the seemingly minor factors in social food choice situations provides deeper insights into consumers' decision processes.…”
Section: Discussionmentioning
confidence: 99%
“…They influence attitudes towards organic purchases, which means that individuals are influenced by the opinions of others towards organic purchases [49]. It is further suggested that subjective norms influence purchase intentions even if people have negative attitudes towards buying sustainably produced food [50].…”
Section: Consequently We Proposementioning
confidence: 99%